Functional interaction between public bodies: Experience of Central Africa countries - Bezuglya, Anna A.; Arutyunyan, Radmila E.; Kolpakova, Elena E.; Mutsalov, Saidakhmed I.; Ngatheyo, Pavel A. C. (Linguistics and Culture Review, 2021)
This paper examines the constitutional approaches accepted in the Central African countries regarding the formalization of interaction between the chambers of parliaments. The study found that all constitutional texts of the considered group of countries as a universal (typical) form of interaction between the chambers of parliament consolidate the adoption of legislative acts; joint meetings (on the taking of their oath by the heads of states or members of the Constitutional Court, making a decision on the introduction of a state of emergency or siege in the country, dismissing the head of state, appointing officials, etc.); the formation of joint commissions and supreme bodies of state power, and the appointment of officials. It was noted that despite the "constitutional equality" of the chambers in terms of introducing bills, financial bills are submitted exclusively to the lower chamber of parliament. The ratification of international treaties by the chambers of parliament (Gabon, Congo) is classified as an atypical (specific) form of interaction between the chambers of parliaments.